Senso comune/buon senso - Cospito, Giuseppe (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2019)
This article deals with Antonio Gramsci’s reflection on the categories of “common sense” and “good sense”, from the pre-prison writings onwards. If in the Gramscian journalistic articles these terms are employed in a loose way, in line with the early twentieth-century usages, a significant reflection can be retraced in the Prison Notebook. On the background of the French and notably Italian discussion on the topic in 1930s, Gramsci develops in his carceral notes an original conception of “common sense” and “good sense”, that illuminates also the notions of philosophy and folklore. The categories are problematicised already in Q 1 and receive a first, provisional sistematisation in 1930-1931. 1932 represents a turning point in the reflection in the categories: on the one hand, there is a reading of common sense (written without quotation marks) that describes the generic middle way between folklore and philosophy (neutral meaning); on the other hand, Gramsci isolates the more specific concepts of “good sense” (positive meaning) and “common sense” (negative meaning), where the quotation marks signal their specific semantic value. In this second meaning, “good sense” is pivotal to understand Gramsci’s philosophy of praxis, as also later occurrences testify. Keywords: Common Sense; Good Sense; Philosophy; Folklore